FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI KABUPATEN/KOTA PROVINSI SUMATERA BARAT - Syaikhul Adlan; Idris Idris; Dewi Zaini Putri (Universitas Negeri Padang, 2015)
This study aims to determine the effect of economic growth, educational level, and the number of people on the unemployment rate on regency / city of West Sumatra during 2011- 2013. Data used in this research is secondary data, in the form of time series (2011-2013) and cross section (19 districts / cities) of West Sumatra province. The results showed: economic growth has a negative impact and no significant effect on the unemployment rate , Level of education has a positive and significant effect on the unemployment rate ,Total population has a positive and significant effect on the unemployment rate and Together economic growth (X1), education level (X2), and population (X3) has a significant impact on the unemployment rate (Y) in the district / city of West Sumatra province..Keyword : unemployment rate, economic growth, education level, popolation